Keeping the Door Open for Young English-speaking Adults in Québec : Language Learning in English Schools and Centres - Advisory Board on English Education (2016)
During a committee hearing in April 2015, Premier Philippe Couillard responded to a question from Mr. David Birnbaum (MNA for D’Arcy-McGee) about “what our government has done and plans to do to ensure that young anglophone Quebecers are full and valued participants in building our future,” by saying that he wanted to hear from the English-speaking community. About the same time, then-Minister of Education Bolduc asked the Advisory Board on English Education (ABEE) to advise him on how to encourage English-speaking youth to remain in Québec. In May 2016, Premier Couillard identified the English educational sector as a model for the system as a whole, and the Board proposed some reasons for this success in its most recent brief. It should be noted that students in the English sector achieve this success while receiving instruction in two languages from kindergarten onward. The ability to function in two languages is recognized as a crucial socio-economic skill for young Anglophones, and has an impact on their decision whether or not to stay in Québec. How can the education system contribute to developing this skill? This brief is respectfully presented to the Minister of Education with recommendations that respond to this question.

One Size Does Not Fit All: Distinct Solutions for Distinct Needs - Advisory Board on English Education (2013)
In this report to the Minister, the Advisory Board on English Education is taking the opportunity to review the themes and concerns identified in earlier correspondence, reports and briefs that continue to describe English education in Québec accurately, and to update them with current examples of both concerns and successes. We emphasize that there is no intention to promote one system over another, nor to assign fault. We believe that many of the inherent difficulties faced by English school boards, schools and centres could be mitigated if MELS were to take better account of the differences between the two sectors in its policies and their implementation. It is hoped that a description of the distinctiveness of the English sector and how it functions differently from the French sector will provide some insight as to how the English system is frequently constrained by many of the Ministry’s policies, especially in their application, and indicate the need for flexibility in implementing policy. This will ensure that the English education system can continue to prepare its graduates to participate fully in the life of Québec society.

Language Learning in the English Schools of Quebec : A Biliteracy Imperative - Advisory Board on English Education (1995)
The school board reorganization, which sooner or later is bound to come about, will force major adjustments on the delivery of English education. The forming of a true English school network through the fusion of the existing Catholic and Protestant structures will provide both an opportunity to strengthen and rationalize the English school system and a challenge to get it right. By getting it right is meant finding an educational mission to which all the constituencies of the English-speaking community and the schools which serve it can respond.